Trauma Immediately Preceding REM-Behavior Disorder: A Valuable Prognostic Marker? - Williams, Stevie R.; Henzler, Nelly; Peřinová, Pavla; Morrison, Ian A.; Ellis, Jason G.; Riha, Renata L. (Frontiers in Neurology, 2021)
Background: Rapid eye movement sleep behaviour disorder (RBD) and trauma-associated sleep disorder (TSD) have considerable symptomatic and clinical overlap. RBD diagnostic criteria also apply to TSD and only a limited number of sleep laboratory confirmed TSD cases are reported in the literature. Study Objectives: To test the hypothesis that REM Sleep Behaviour Disorder (RBD) secondary to trauma is more closely related to Trauma associated Sleep Disorder (TSD) compared to idiopathic RBD (iRBD) without trauma in the general population. Methods: A retrospective cohort study of 122 consecutive RBD patients (103 males) at two tertiary sleep clinics in Europe between 2005 and 2020 was studied. Patients were diagnosed as having iRBD by video polysomnography and had a semi-structured interview at presentation, including specifically eliciting any history of trauma. Patients with secondary RBD were excluded from the study. Patients with iRBD were categorised into three groups according to reported trauma history: 1) No history of trauma, 2) traumatic experience at least 12 months prior to RBD symptom onset and 3) traumatic experience within 12 months of RBD symptom onset. iRBD duration was defined as the interval between estimated onset of RBD symptoms and last hospital visit or death. Follow-up duration was defined as the interval between iRBD diagnosis and last hospital visit or death. Results: In a follow-up period of up to 18 years, no patient who experienced trauma within 12 months preceding their iRBD diagnosis received a diagnosis of a neurodegenerative disorder (n=35), whereas 38% of patients without trauma within the 12 months of symptom onset developed a neurodegenerative illness. These patients were also significantly more likely to have a family history of α-synucleinopathy or tauopathy. Conclusions: The development of RBD within 12 months of experiencing a traumatic life event, indistinguishable clinically from iRBD, did not lead to phenoconversion to a neurodegenerative disorder even after 18 years. We suggest that the criteria for TSD be reviewed in the light of these findings. The other option would be to establish a sub-type of RBD classified as secondary RBD due to trauma.